Prevalence of frailty and reliability of established frailty instruments in adult elective colorectal surgical patients: a prospective cohort study. Issue 1160 (12th January 2021) - Dale MacLaine, Thomas; Baker, Oliver; Burke, Dermot; Howell, Simon J
Abstract: Purpose: Large population studies now demonstrate that frailty is prevalent in all adult age groups. Limited data exist on the association between frailty and surgical outcome in younger patients. The aim of the study was to explore the agreement between frailty identification tools and collect pilot data on their predictive value for frailty-associated outcomes in an adult surgical population. Study design: Prospective cohort study. Results: Frailty scores were recorded in 200 patients (91 men), mean (range) age 57 (18–92) years. The prevalence of prefrailty was 52%–67% and that of frailty 2%–32% depending on the instrument used. Agreement between the instruments was poor, kappa 0.08–0.17 in pairwise comparisons. Outcome data were available on 160 patients. Only the frailty phenotype was significantly associated with adverse outcomes, RR 6.1 (1.5–24.5) for postoperative complications. The three frailty scoring instruments studies had good sensitivity (Clinical Frailty Scale (CFS)—90%, Accumulation Deficit (AD)—96%, Frailty Phenotype (FP)—97%) but poor specificity (CFS—12%, AD—13%, FP—18%) for the prediction of postoperative complications. All three instruments were poorly predictive of adverse outcomes with likelihood ratios of CFS—1.02, AD—1.09 and FP—1.17. Conclusions: This study showed a significant prevalence of prefrailty and frailty in adult colorectal surgical patients of all ages. There was poor agreement between three established frailty scoring instruments. Our data do not support the use of current frailty scoring instruments in all adult colorectal surgical patients. However, the significant prevalence of prefrailty and frailty across all age groups of adult surgical patient justifies further research to refine frailty scoring in surgical patients.